Kaji Eksperimen Perbandingan Konsumsi Bahan Bakar Sistem Injeksi dan Karburator dengan Variabel Bobot Pengendara - Santoso, Budi; , Ir.Tri Tjahjono, MT (2016)
Fuel supply system on the combustion system on the engine 4 stroke is the most fundamental in the determination of a series of work the motor. The emergence injection system that replaced the carburetor system replacement by EFI aims to be a vehicle to be frugal. The dilemma size economical comparison between EFI and carburetor is still difficult to understand by the user in broad scale, especially motorcycles Mio Fino (EFI) in 2014 that in this occasion becomes the test device. By using variable rider weight, the ratio of the intended economical will be measured with certainty. Research done by driving both types pengkabutan both carburetor and EFI in a relatively straight path and the elevation difference is not too big ketinggianya. The study begins by providing premium fuel into the tank as much as 100 cc motorcycle and its rider and then driven up to speeds of 30 km / h then the motor is turned on. At this time started recording the length of time and the distance with a variable number of revolutions of 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, up to 6000 rpm and the variable rider weight 40 kg, 60 kg and 80 kg made of at least three times in each of variables. Results of experiments concluded that the weight of the rider also contribute part as a measure of how efficient these misting systems and misting systems injection less consumption at any one work cycle. And the best achievements in the rider weighing 40 kg which spent fuel premium 100 cc with a consumption of 5.27 minutes to cover a distance of 4.3 km with an average speed of 45.8 km / h. Thus it can be concluded that the misting system more efficient injection of carburetor misting system. This is because the injection misting system can break down particles of fuel is better and smaller than the carburetor misting system. So that the particle surface more extensive fuel and air are attached to the fuel will be more and more. So the comparison Air Fuel Ratio (AFR) will be perfectly mixed in pengaplikasianya in the combustion process that occurs in the combustion chamber